Organizational factors and total quality management - an empirical study - Joseph, I. Nelson; Rajendran, Chandrasekharan; Kamalanabhan, T. J.; Anantharaman, R. N. (Taylor & Francis, 1999)
The level of awareness of Total Quality Management (TQM) has increased considerably over the last few years. Different sets of organizational requirements are prescribed by quality management gurus and practitioners for the effective practice of TQM. These requirements do not seem to have been formulated on the basis of systematic empirical research. Many researchers point out that tacit factors, e.g. employee empowerment, open culture and executive commitment, and not TQM tools and techniques alone, could drive TQM success, and that organizations would need to acquire these factors to stay successful. Many TQM advocates have also suggested that a conducive organizational environment would be essential for an effective practice of TQM. However, they did not offer any empirical evidence. There appears to be no empirical study reported in the literature that could establish a relation between TQM and organizational factors. The objective of this paper is to describe an empirical research on TQM conducted in Indian business units carried out recently by considering some organizational factors, e.g. quality of work life, organizational climate and communication. The methodology and findings are discussed in detail.